Analisis Ketersediaan Sistem Pembangkit Berbasiskan Pembangkit Listrik Tenaga Angin (PLTB) Dan Pembangkit Listrik Tenaga Surya (PLTS) - Herki Desrizal; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The increasing need for energy and the depletion of petroleum reserves forces people to seek alternative energy sources. Based on the above problems it is necessary to analyse of the availability of generating systems to generate electrical energy pekanbaru city. This study uses a HOMER simulation consisting of Solar Cell (PV), Wind, and Converter. Simulation results of the highest availability of solar energy at 12.00 for 3.86 kw, and wind energy at 16.00 for 3.79 kw.for grouping of the potential winds are in group II that is locations with an average wind speed of 2,5 – 4 m/s. the resulting solar energy can be used for small scale electrical energy conversion system.Design of wind turbine (PLTB) and solar power plants the most optimal based on net present cost of 53.18 and cost of energy (COE) amount 506./kWh. In terms of its economy, the greater the installed renewable energy capacity, will decrease fuel usage levels and cost incurred.Keywords: PV, Wind, renewable energy, HOMER, Optimazation, Sensitivity, Availability